The Bulgarian Government’s Efforts to Address The Issue of Transnational Organized Crime: Trafficking in Human Beings and Smuggling Migrants - Satria, Dendy Perwira Dhira; Sadadi, Puguh (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Human trafficking and migrant smuggling are forms of transnational organized crime (TOC) that affect people all over the world, including in Bulgaria. The actions taken by the Bulgarian government to combat these illegal operations are the focus of this study. A more effective evaluation of Bulgaria's involvement within the regional security complex can be achieved by employing qualitative approaches with the Regional Security Complex Theory (RSCT) and applying primary and secondary data collection methods. Institutionalization, increased border surveillance, and public education initiatives are among the steps highlighted in the report. Understanding Bulgaria's anti-crime activities has been enhanced by this analysis, which provides valuable information for improving policies against migrant smuggling and human trafficking.